5(3x-1)-5=13x+2

Simple and best practice solution for 5(3x-1)-5=13x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x-1)-5=13x+2 equation:


Simplifying
5(3x + -1) + -5 = 13x + 2

Reorder the terms:
5(-1 + 3x) + -5 = 13x + 2
(-1 * 5 + 3x * 5) + -5 = 13x + 2
(-5 + 15x) + -5 = 13x + 2

Reorder the terms:
-5 + -5 + 15x = 13x + 2

Combine like terms: -5 + -5 = -10
-10 + 15x = 13x + 2

Reorder the terms:
-10 + 15x = 2 + 13x

Solving
-10 + 15x = 2 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
-10 + 15x + -13x = 2 + 13x + -13x

Combine like terms: 15x + -13x = 2x
-10 + 2x = 2 + 13x + -13x

Combine like terms: 13x + -13x = 0
-10 + 2x = 2 + 0
-10 + 2x = 2

Add '10' to each side of the equation.
-10 + 10 + 2x = 2 + 10

Combine like terms: -10 + 10 = 0
0 + 2x = 2 + 10
2x = 2 + 10

Combine like terms: 2 + 10 = 12
2x = 12

Divide each side by '2'.
x = 6

Simplifying
x = 6

See similar equations:

| (7a-a)-2=40 | | 8x+7y=-12 | | 7k+29=-11y | | 2/100=4/x | | 129+0.25m=216.50 | | -23.14+12.6= | | 10x+35+4x=315 | | 5(7x+1)=285 | | -102=2(3+6n) | | d^2-19de+48e=0 | | 4(0)-10y=20 | | .9X+19.3=5.3-2.6X | | -1.8=.54 | | 9x-12x=-8-10 | | Y=15x^2+1x | | 86h^2+46h=0 | | 49p^2-49p=0 | | 3/4x=1200000 | | 4+5-12=0 | | 49p^2+49p=0 | | 0.75x^2+1=16 | | 32x=90 | | 4+3=2x | | 8(2x+1)=4x+48 | | 15-5a=-10 | | 28p^2-29p=0 | | 7/4=(6/c)-2 | | 16-8x-16-2x=2x-8-8x-16 | | 7(5g+2)=21 | | -19+2t=15-3t | | 2v^2-15v+13=0 | | -6x+-3-3x-4= |

Equations solver categories